2010
DOI: 10.2166/wst.2010.757
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and evaluation of removal of pathogens at municipal wastewater treatment plants

Abstract: The concentrations and removal of Cryptosporidium, Giardia, and microbial indicators, including somatic coliphages and fecal coliforms were investigated through the wastewater treatment processes at three municipal wastewater treatment plants in Beijing, China. The experimental results showed that the concentrations of Cryptosporidium in untreated wastewater, primary treatment effluent, secondary treatment effluent, tertiary treatment effluent were 33-600, 67-333, 0-9 and 0-0.4 oocysts L(-1), and that of Giard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…3.1.4.2 Primary /preliminary treatment The primary treatment performed in wastewater treatment plants does not produce a significant reduction in pathogens. A reduction of 0.06 log 10 units for fecal coliforms was observed after a primary sedimentation treatment in a full-scale waste water treatment plant (Fu et al, 2010) (Table 9).…”
Section: Wastewater Treatment and Resource Recoverymentioning
confidence: 99%
See 2 more Smart Citations
“…3.1.4.2 Primary /preliminary treatment The primary treatment performed in wastewater treatment plants does not produce a significant reduction in pathogens. A reduction of 0.06 log 10 units for fecal coliforms was observed after a primary sedimentation treatment in a full-scale waste water treatment plant (Fu et al, 2010) (Table 9).…”
Section: Wastewater Treatment and Resource Recoverymentioning
confidence: 99%
“…Oxidation ditch treatment produced a reduction of around 2.5 log 10 units for fecal coliforms (Fu et al, 2010). Combined sewers carry wastewater from urban areas as well as storm water runoff in the same pipe.…”
Section: Oxidation Ditchmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrating that giardiasis occurs more frequently than cryptosporidiosis in Norway. Fu et al (2010) investigated the performance of three WTPs in Beijing, China, by determining the concentrations of fecal indicators and pathogenic protozoa. According to their study, Cryptosporidium and Giardia densities in untreated wastewater varied from 33 to 600 oocysts/L and 130 to 3,600 cysts/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Nasser et al (2012) reported that in 23 out of 30 studies, all tested raw wastewater samples were positive for Giardia, at concentrations ranging from 2.3 to 1,000,000 cysts/10 L, showing that Giardia pollution is quite universal and requires effective control to secure the biological safety of reclaimed water. Giardia concentrations in raw wastewater and primary, secondary and tertiary treatment effluents were 1300-36,000, 5330-20,330, 0-320 and 0-21 cysts/10 L, respectively, in three municipal wastewater treatment plants in Beijing, China (Fu et al, 2010). Thus, significant removals of Giardia were achieved through secondary and tertiary treatment, showing the importance of establishing multiple barriers for pathogen control.…”
Section: Occurrence Of Giardia In Reclaimed Water Samplesmentioning
confidence: 97%